Peningkatan hasil belajar siswa dengan menggunakan metode bermain peran dalam pembelajaran PKn - Sarniyati Sarniyati (SCHOULID: Indonesian Journal of School Counseling, 2019)
The conditions of learning in elementary schools, especially Civics Education at this time still use a lot of conventional learning models (Lecture method). In learning, students only become objects, so it does not encourage the potential of students to develop. Civics Learning with the use of the role-playing method in grade V elementary school is very good to apply. It aims to make students able to portray something to the front of the class, have an attitude of respect for others, be creative, learn to solve a particular problem and be able to get along in a group environment and social life. The results showed that there was an increase in students' abilities in learning by using role-playing. This is indicated by the increase in results in the form of grades obtained by students, namely the value in the first cycle based on the assessment of results with an average of 6.96. While the value of the implementation of learning in the second cycle increased by 8.57. At the learning planning stage, the teacher's ability to design learning plans increases. This is reflected in (1) the learning plan includes things that form the basis of planning, (2) the learning plan is prepared based on the education unit level curriculum by taking into account the interests and needs of students, (3) the learning plan has included learning tasks as a clear and detailed that supports the achievement of objectives.